Respuesta :
I.
First, plug in the number two in the place of x.
f(2) = 3(2) + 2.
Simplify
f(2) = 6+2
f(2) = 8
II.
First, we need to find the inverse function of x.
To do this, we begin by replacing f(x) with y, and switching the x and y values.
y= (2x-7)/3
x= (2y-7)/3
Then we solve for y.
3x = 2y-7
3x + 7 = 2y
(3x+7)/2 = y
Replace y with f^-1(x)
f^-1(x)= (3x+7)/2
Now that we have the inverse function, plug in 3 for x.
f^-1(x) = (3(3) + 7)/2
f^-1(x) = (9+7)/2
f^-1(x) = 16/2 = 8.
III. 2y+14 = 4y-2
Solve for y
14 = 2y - 2
16 = 2y
y = 8
So, since all of the statements have the result of 8, then all the statements have the same result.
Hope this helps!
First, plug in the number two in the place of x.
f(2) = 3(2) + 2.
Simplify
f(2) = 6+2
f(2) = 8
II.
First, we need to find the inverse function of x.
To do this, we begin by replacing f(x) with y, and switching the x and y values.
y= (2x-7)/3
x= (2y-7)/3
Then we solve for y.
3x = 2y-7
3x + 7 = 2y
(3x+7)/2 = y
Replace y with f^-1(x)
f^-1(x)= (3x+7)/2
Now that we have the inverse function, plug in 3 for x.
f^-1(x) = (3(3) + 7)/2
f^-1(x) = (9+7)/2
f^-1(x) = 16/2 = 8.
III. 2y+14 = 4y-2
Solve for y
14 = 2y - 2
16 = 2y
y = 8
So, since all of the statements have the result of 8, then all the statements have the same result.
Hope this helps!
my handwriting is a bit bad sorry but im sure I got the right answer here
![Ver imagen HunnidBandzWeUp](https://us-static.z-dn.net/files/dce/842cd23853aa2e472b5807772797e1ba.jpg)